2022
DOI: 10.1080/10717544.2022.2056663
|View full text |Cite
|
Sign up to set email alerts
|

Nanodelivery of essential oils as efficient tools against antimicrobial resistance: a review of the type and physical-chemical properties of the delivery systems and applications

Abstract: This review provides a synthesis of the last ten years of research on nanodelivery systems used for the delivery of essential oils (EOs), as well as their potential as a viable alternative to antibiotics in human and veterinary therapy. The use of essential oils alone in therapy is not always possible due to several limitations but nanodelivery systems seem to be able to overcome these issues. The choice of the essential oil, as well as the choice of the nanodelivery system influences the therapeutic efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 81 publications
(234 reference statements)
0
34
0
Order By: Relevance
“…Rapid dissolution of the initial burst could have caused the instant burst of molecules of essential oil molecules adsorbed to the surface of the polymer [ 35 ]. Studies suggest that polymer degradation is the primary mechanism by which CSNPs release essential oils into the external environment [ 45 ]. The slower release phase is caused by the diffusion of encapsulated essential oil molecules from the nanoparticle core to the dissolution medium through interconnected pores and channels in the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Rapid dissolution of the initial burst could have caused the instant burst of molecules of essential oil molecules adsorbed to the surface of the polymer [ 35 ]. Studies suggest that polymer degradation is the primary mechanism by which CSNPs release essential oils into the external environment [ 45 ]. The slower release phase is caused by the diffusion of encapsulated essential oil molecules from the nanoparticle core to the dissolution medium through interconnected pores and channels in the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, CO-SLNs were prepared in order to improve its physicochemical and antimicrobial properties. Several investigations have confirmed the positive influence of lipid carriers on increasing the antimicrobial effectiveness of herbal oils [24][25][26]. Also, various cinnamon oil loaded nano delivery systems have been developed including Nanostructured lipid carriers (NLC) [27], alginate-calcium nano/micro particle [28], chitosan nanoparticles [29], etc.).…”
Section: Introductionmentioning
confidence: 98%
“…Natural plant extracts are used in the food industry as alternative preservatives. It is possible to prevent or delay some chemical spoilage that occurs during food storage with the use of 10.3389/fmicb.2022.1092248 small amounts of EOs that are potential antioxidants due to their radical scavenging activities (Dupuis et al, 2022). Mariotti et al (2022) confirmed the importance of evaluating natural products to consolidate the idea of safe EO applications in reducing and preventing intensive livestock infections.…”
Section: The Preservative Effects Of Eos On Chicken and Seafood Productmentioning
confidence: 96%